HUBUNGAN KUALITAS TIDUR DENGAN MEMORI JANGKA PENDEK SANTRI MA YAJRI DI PONDOK PESANTREN SIROJUL MUKHLASIN 2 PAYAMAN - yaneka aldi putra; Erna Erawati; Suyanta suyanta; Angga Sugiarto (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Background: The students was categorized as the group of teenagers who most often experienced sleep disturbances. Poor sleep period will cause disruption of brain functions such as memory disorders. Of the several types of memory that are most affected short-term memory, previous studies on short-term memory and sleep quality have yielded mixed and mixed results. Purpose: Knowing the relationship between sleep quality and short-term memory students. Method: This research is quantitative with an analytical observational design using a cros sectional study approach. Data collection uses a simple random sampling the sample is 67 respondent and technique sleep quality was measured by the PSQI (Pittsburgh Sleep Quality Index) questionnaire and working memory was measured by the Span Digit Test. Result: Respondents with good sleep quality were 21 people (31.3%) while 46 people (68.7%) had poor sleep quality. There are 33 people with low memory (49.3%) and 34 people with high memory (50.7%). Conclusion: There is a significant relationship between sleep quality and short-term memory students, with a significance value of chi square test p= 0.001 (p <0.05). Keywords: Students, sleep quality, short-term memory.